2011
DOI: 10.5251/ajfn.2011.1.4.185.192
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between eating behaviours, body image and BMI status among adolescence age 13 to 17 years in Meru, Klang, Malaysia

Abstract: The purpose of this study was to examine how body image, Body Mass Index (BMI), and eating attitudes were related among adolescence age 13 to 17 years old. The samples were made up of 356 adolescents, where 165 (46.3%) were male while 191(53.7%) were female. Body image was assessed using the Figure Rating Scale (Stunkard et al., 1983), BMI was calculated based on measures of height and weight, and eating behaviour was assessed using Eating Behaviour Patterns Questionnaire (EBPQ). This study has contributed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
1
2
0
2
Order By: Relevance
“…Likewise, Ozmen et al [53] indicated that boys desired a larger body size. Furthermore, the association between body shape dissatisfaction and obesity was found in several studies in Malaysia [48,54,55]. Meanwhile, the present findings showed that there was an association between respondents under-estimating their body weight status and overweight and obese status.…”
Section: Discussionsupporting
confidence: 72%
“…Likewise, Ozmen et al [53] indicated that boys desired a larger body size. Furthermore, the association between body shape dissatisfaction and obesity was found in several studies in Malaysia [48,54,55]. Meanwhile, the present findings showed that there was an association between respondents under-estimating their body weight status and overweight and obese status.…”
Section: Discussionsupporting
confidence: 72%
“…5 In this study we used the preliminary version of this questionnaire from UtahState University. 16 This questionnaire consists of 51 selfreport items on healthy and unhealthy eating behaviors. Every item was rated in a 5-point Likertscale ranging from strongly disagree to strongly agree.…”
Section: Study Instrumentmentioning
confidence: 99%
“…Por otro lado, se encontró correlación positiva entre en el IMC/Edad y los conocimientos, actitudes y prácticas acerca de la alimentación saludable en los adolescentes. Nuestros resultados son similares con hallazgos encontrados en otros estudios 15,22,[27][28][29] . Efectivamente, tener un conocimiento adecuado, actitudes favorables y prácticas alimentarias adecuadas podría jugar un papel importante en la mejora los hábitos alimenticios en los adolescentes 28 .…”
Section: Variablesunclassified
“…Nuestros resultados son similares con hallazgos encontrados en otros estudios 15,22,[27][28][29] . Efectivamente, tener un conocimiento adecuado, actitudes favorables y prácticas alimentarias adecuadas podría jugar un papel importante en la mejora los hábitos alimenticios en los adolescentes 28 . Además, esto podría influir de manera positiva en la selección de alimentos saludables y, en consecuencia, favorecer un estado nutricional adecuado.…”
Section: Variablesunclassified